Covid-19: Potential relationship of anosmia and ageusia in swallowing rehabilitation (International Journal of Medical and Surgical Sciences, 2023)
Anosmia and ageusia are prevalent symptoms in COVID-19 patients and can last for weeks. Sensory and olfactory functions perform an important role in swallowing.This article proposes the possible negative effect of the symptoms of anosmia and ageusia in the swallowing rehabilitation of dysphagia oropharyngeal and post-intubation in patients with COVID-19. It is important to consider that swallowing is a multisensory and pathological process, where taste and smell play a key role. In accordance with these factors, we propose future research incorporating objective evaluation methods of the affected senses in COVID-19 patients.
Keywords: SARS-CoV-2; COVID-19; anosmia; ageusia; deglutition disorders; airway extubation